2019
DOI: 10.1111/ors.12408
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell ameloblastoma in a paediatric patient: a case report and review of oral basal cell tumours

Abstract: Basal cell ameloblastoma (BCA) is a rare histological variant of ameloblastoma. It is composed of densely packed nests and strands of basaloid cells with inconspicuous stellate reticulum‐like cells. To date, there are only 24 reported cases of BCA in the English language literature. Ameloblastoma in children is relatively an uncommon tumour and accounts for approximately 15% among all odontogenic tumours. We report a case of BCA in an 8‐year‐old Iban girl who underwent hemimandibulectomy and reconstruction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Hence, it is difficult to understand nature and clinicopathological relation. [ 9 ] We did a PubMed and google scholar database search for basal cell variant of ameloblastoma [ Table 1 ]. [ 2 7 10 11 12 13 14 15 16 17 18 19 20 21 22 23 ] We found that most of the reported cases of BCA were seen in the 3 rd to 5 th decade, and the maxilla to mandible ratio reported was 1:1.2 with no gender predilection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is difficult to understand nature and clinicopathological relation. [ 9 ] We did a PubMed and google scholar database search for basal cell variant of ameloblastoma [ Table 1 ]. [ 2 7 10 11 12 13 14 15 16 17 18 19 20 21 22 23 ] We found that most of the reported cases of BCA were seen in the 3 rd to 5 th decade, and the maxilla to mandible ratio reported was 1:1.2 with no gender predilection.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the peripheral cell nuclei can be seen. [ 9 20 ] Histopathologically, differential diagnosis can be intraoral basal cell carcinoma and basal cell adenoma. [ 2 25 ] Immunohistological (IHC) studies have been conducted on variants of ameloblastoma including six cases of BCA.…”
Section: Discussionmentioning
confidence: 99%